Earlobe crease as a marker of coronary heart disease: a systematic review - Jonathan Ricardo Hamonangan; Fitri Agustina Huspa; Rien Afrianti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Earlobe crease (ELC) is a wrinkle-line in the skin that surrounds the ear approximately one third of the length between the tragus and the posteroinferior edge of the earlobe. Since the first study in 1973, the relationship between ELC and coronary heart disease (CHD) remains unclear. In addition, the pathogenesis of ELC has not well described, yet. This review aimed to evaluate the relationship between CHD and the presence of ELC using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol. Eligible studies obtained from PubMed and Google Scholar using relevant keywords were collected. The assessment of quality of the studies was carried out based on the National Heart Lung and Blood Institute. Among 21 studies collected, 19 studies reported a correlation between the ELC and CHD indicating that ELC as a potential marker of CHD. Seven studies reported a significant association of ELC with CHD after adjusting confounding variables such as age, sex and other risk factors for atherosclerosis in analysis. Seven studies reported that subjects with ELC had more significantly severe CHD based on coronary angiography. The sensitivity of the ELC was reported between 30-98% and the specificity between 43-91%. Two studies reported no relationship between ELC and CHD after adjustment of age in analysis. Earlobe crease is a dermatological sign which was reported to have potential as a marker of CHD. Further study with large sample in population from various ethnics is needed in order to obtain a robust conclusion regarding the clinical importance of ELC in predicting CHD.